2018
DOI: 10.1111/epi.14051
|View full text |Cite
|
Sign up to set email alerts
|

User‐based evaluation of applicability and usability of a wearable accelerometer device for detecting bilateral tonic–clonic seizures: A field study

Abstract: Clinical validation studies of seizure detection devices conducted in epilepsy monitoring units (EMUs) can be biased by the artificial environment. We report a field (phase 4) study of a wearable accelerometer device (Epi-Care) that has previously been validated in EMUs for detecting bilateral tonic-clonic seizures (BTCS). Seventy-one patients using the device (or their caregivers) completed the modified Post-Study System Usability Questionnaire. Median time patients had been using the device was 15 months (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 13 publications
(30 reference statements)
1
65
1
Order By: Relevance
“…It is likely that a better sensitivity could have been achieved at the expense of a higher false positive rate. As it is, the daily false positive detection rates seen during our study were over an order of magnitude lower than those reported with the use of wrist‐worn devices in the home environment . Acceptable values for sensitivity and false detection rates for a device to be used to detect seizures in dogs have not been established.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…It is likely that a better sensitivity could have been achieved at the expense of a higher false positive rate. As it is, the daily false positive detection rates seen during our study were over an order of magnitude lower than those reported with the use of wrist‐worn devices in the home environment . Acceptable values for sensitivity and false detection rates for a device to be used to detect seizures in dogs have not been established.…”
Section: Discussioncontrasting
confidence: 67%
“…Initial validation of the technology was performed in hospitalized patients admitted to long‐term video‐electroencephalography (EEG) monitoring units, during which all seizure activity was confirmed by EEG and all movements recorded, with reported sensitivity ranging from 85 to 100% and a false detection rate of 0.2‐1/day . A subsequent field study designed to evaluate the use of the device in the home environment reported a mean sensitivity of 85% and a mean false detection rate of 1.4/day . A major objective for use of these devices in humans is the detection of severe nocturnal seizures, in order to enable intervention and lead to the prevention of sudden unexpected death in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface EMG is typically used for detecting convulsive seizures, with 2 large-scale blinded prospective studies demonstrating high sensitivity (76%-100%) with average false-alarm rate ranging from 0.7 to 2.5/24 h. 7 Movement-based GTCS detection, primarily using accelerometry sensors, is associated with highly variable sensitivity (31%-95%) and positive predictive value (4%-60%) across video-EEG studies, whereas a field study reported even lower sensitivity (14%). 8 Conversely, 2 other field studies with high sensitivity are reported in this supplement: one using accelerometry showed a median sensitivity of 90% and a false alarm rate of only 0.1/d for GTCS detection, 10 whereas another one using video-only in a residential care setting reported 100% sensitivity and a median false alarm rate of 0.78 per night. 11 Multimodal seizure detection is currently characterized by various sensing methods and highly variable sensitivity (4%-100%) and rate of false alarms (0.25-20 per 8 hours).…”
mentioning
confidence: 95%